2019
DOI: 10.1155/2019/1392020
|View full text |Cite
|
Sign up to set email alerts
|

Zhujie Hewei Granules Ameliorated Reflux Esophagitis in Rats

Abstract: Background. Gastroesophageal reflux disease (GERDs) is a common chronic digestive system disease, in which the symptoms of reflux esophagitis (RE) seriously affect the quality of life. Aims. We aimed to study the therapeutic effect of Zhujie Hewei granules (ZHG) on reflux esophagitis in model rats. Materials and Methods. A rat model of RE was established with the steps of half pylorus ligation, cardiotomy, and hydrochloric acid perfusion. The rats in treatment groups were orally administered with 1.30, 2.60, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…However, these drugs have been reported to have no significant results in 20~30% of patients, and the main pathogenic factors cannot be reduced, making complete treatment difficult. In addition, it is known that serious complications occur when used for a long time [ 32 , 33 ]. Therefore, in the current study, research on traditional Korea medicine that shows benefits in reducing recurrence and side effects and alleviating symptoms has been actively conducted [ 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these drugs have been reported to have no significant results in 20~30% of patients, and the main pathogenic factors cannot be reduced, making complete treatment difficult. In addition, it is known that serious complications occur when used for a long time [ 32 , 33 ]. Therefore, in the current study, research on traditional Korea medicine that shows benefits in reducing recurrence and side effects and alleviating symptoms has been actively conducted [ 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that gastrointestinal hormones play an important role in the regulation of gastrointestinal function [25–27] . GAS, the first identified gastrointestinal peptide, is essential in certain digestive processes, such as gastric acid secretion and intestinal motility [28,29] .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that gastrointestinal hormones play an important role in the regulation of gastrointestinal function. [25][26][27] GAS, the first identified gastrointestinal peptide, is essential in certain digestive processes, such as gastric acid secretion and intestinal motility. [28,29] MTL is involved in food intake regulation, stimulating the contractile movements of the gastric sinus and fundus, and promoting the contraction of the smooth muscle of the gastrointestinal tract.…”
Section: Effect Of Dashanzha Pill On Gastrointestinal Hormonesmentioning
confidence: 99%
“…[ 14 ] Also, they could improve the pH value of gastric contents, decrease the gastrointestinal hormones, and improve the inflammatory damage in rats. [ 15 ] A combination of Chinese herbal formula and western medicine against GERD could significantly improve the treatment effect and reduce the side effects of western medicine.…”
Section: Discussionmentioning
confidence: 99%